A comparison of two different feeding methods for Yinzhihuang oral liquid in the treatment of neonatal jaundice (茵栀黄口服液治疗新生儿黄疸中两种不同喂药方法的效果比较) - SONG Huifang (宋慧芳); LIU Yanlin (刘艳林); DOU Wei (窦玮); ZHOU Wei (周伟) (中西医结合护理)
Objective To evaluate two different feeding methods for Yinzhihuang oral liquid in the treatment of neonatal jaundice. Methods Totally 200 neonatal jaundice cases requiring oral administration of Yinzhihuang oral liquid were randomly divided into the control group and the observation group, with 100 cases in each group. The disposable 5ml syringe was used to feed neonates with Yinzhihuang oral liquid in the control group, and the disposable pacifier was used as an auxiliary feeding device in the observation group. The adverse reactions to oral administration and length of time spent in medication were recorded. Results The incidences of choking cough, vomiting and overflowing drug liquid in the observation group were lower than those in the control group (P＜0. 05), and length of time spent in medication was shorter in the observation group were lower than that in the control group (P＜0. 05). Conclusion In the treatment of neonatal jaundice, the combined use of disposable pacifier and disposable syringe is effective to reduce the risk of choking cough, vomiting and overflowing drug liquid, and shorten the length of time spent in oral medication. (目的 对比两种不同喂药方法在茵栀黄口服液治疗新生儿黄疸中的应用效果。方法 选取入住新生儿科的200例需要口服茵栀黄的黄疸患儿, 随机分为2组, 对照组(n=100)采用一次性5 mL注射器喂药, 观察组(n=100)采用一次性奶嘴辅助一次性注射器喂药。对比2组黄疸患儿的反应、喂药时间等方面的差异。结果 观察组黄疸患儿呛咳、呕吐、溢药等不良反应发生率低于对照组, 喂药所需时间较对照组少, 差异有统计学意义(P＜0. 05)。结论 茵栀黄口服液治疗新生儿黄疸中, 采用一次性奶嘴辅助一次性注射器能有效降低新生儿呛咳、呕吐、溢药的发生风险, 缩短口服给药所需时间。)